Genome-Wide Transcriptome Analysis Reveals Intermittent Fasting-Induced Metabolic Rewiring in the Liver - Gavin Yong-Quan Ng; Sung-Wook Kang; Joonki Kim; Asfa Alli-Shaik; Sang-Ha Baik; Dong-Gyu Jo; M. Prakash Hande; Christopher G. Sobey; Jayantha Gunaratne; David Yang-Wei Fann; Thiruma V. Arumugam (SAGE Publishing, 2019)
Scope: Intermittent fasting (IF) has been extensively reported to promote improved energy homeostasis and metabolic switching. While IF may be a plausible strategy to ameliorate the epidemiological burden of disease in many societies, our understanding of the underlying molecular mechanisms behind such effects is still lacking. The present study has sought to investigate the relationship between IF and changes in gene expression. We focused on the liver, which is highly sensitive to metabolic changes due to energy status. Mice were randomly assigned to ad libitum feeding or IF for 16 hours per day or for 24 hours on alternate days for 3 months, after which genome-wide transcriptome analysis of the liver was performed using RNA sequencing. Our findings revealed that IF caused robust transcriptomic changes in the liver that led to a complex array of metabolic changes. We also observed that the IF regimen produced distinct profiles of transcriptomic changes, highlighting the significance of temporally different periods of energy restriction. Our results suggest that IF can regulate metabolism via transcriptomic mechanisms and provide insight into how genetic interactions within the liver might lead to the numerous metabolic benefits of IF.